Bridge Between Neuroimmunity and Traumatic Brain Injury - Kelso, Matthew L. (2014)
The pathophysiology of degenerative, infectious, inflammatory and traumatic diseases of the central nervous system includes a significant immune component. As to the latter, damage to the cerebral vasculature and neural cell bodies, caused by traumatic brain injury (TBI) activates innate immunity with concomitant infiltration of immunocytes into the damaged nervous system. This leads to pro-inflammatory cytokine and prostaglandin production and lost synaptic integrity and more generalized neurotoxicity. Engagement of adaptive immune responses follows including the production of antibodies and lymphocyte proliferation. These affect the tempo of disease along with tissue repair and as such provide a number of potential targets for pharmacological treatments for TBI. However, despite a large body of research, no such treatment intervention is currently available. In this review we will discuss the immune response initiated following brain injuries, drawing on knowledge gained from a broad array of experimental and clinical studies. Our discussion seeks to address potential therapeutic targets and propose ways in which the immune system can be controlled to promote neuroprotection.